Stokes and anti-Stokes luminescence of Er3+ doped Ga10Ge25S65 glass excited at 980 and 532 nm - Frej, Milena L.; Valdez, Ernesto; de Araujo, Cid B.; Ledemi, Y. [UNESP]; Messaddeq, Younes [UNESP] (American Institute of Physics (AIP), 2010)
We report on photoluminescence (PL) properties of Er3+ doped Ga10Ge25S65 glass. Experiments were performed using 5 ns laser pulses at 980 nm (532 nm), in resonance with the I-4(15/2)-> I-4(11/2) (I-4(15/2)-> H-2(11/2)) transition of the Er3+ ions. PL bands were observed from the blue to the near-infrared and the dependence of their intensity as a function of the laser intensity was analyzed. The PL temporal behavior was analyzed through rate equations for the population densities and using the Inokuti-Hirayama model. The results allowed identification of the PL pathways and the characterization of energy transfer processes involving pairs of ions. (C) 2010 American Institute of Physics. [doi:10.1063/1.3493239]